Comparison of Activity Profiles and Physiological Demands Between International Rugby Sevens Matches and Training. Issue 5 (May 2016) - Higham, Dean G.; Pyne, David B.; Anson, Judith M.; Hopkins, Will G.; Eddy, Anthony
Abstract : Abstract: Higham, DG, Pyne, DB, Anson, JM, Hopkins, WG, and Eddy, A. Comparison of activity profiles and physiological demands between international rugby sevens matches and training. J Strength Cond Res 30(5): 1287–1294, 2016—The specificity of contemporary training practices of international rugby sevens players is unknown. We quantified the positional group-specific activity profiles and physiological demands of on-field training activities and compared these with match demands. Twenty-two international matches and 63 rugby-specific training drills were monitored in 25 backs and 17 forwards from a national squad of male rugby sevens players over a 21-month period. Drills were classified into 3 categories: low-intensity skill refining ( n = 23 drills, 560 observations), moderate- to high-intensity skill refining ( n = 28 drills, 600 observations), and game simulation ( n = 12 drills, 365 observations). Movement patterns (via Global Positioning System devices) and physiological load (via heart rate monitors) were recorded for all activities, and the differences between training and matches were quantified using magnitude-based inferential statistics. Distance covered in total and at ≥3.5 m·s −1, maximal velocity, and frequency of accelerations and decelerations were lower for forwards during competition compared with those for backs by a small but practically important magnitude. No clear positional group differences were observed for physiological load during matches. Training demands exceeded match demands only for frequency of decelerations of forwards during moderate- to high-intensity skill-refining drills and only by a small amount. Accelerations and distance covered at ≥6 m·s −1 were closer to match values for forwards than for backs during all training activities, but training drills consistently fell below the demands of international competition. Coaches could therefore improve physical and physiological specificity by increasing the movement demands and intensity of training drills.